Catherine Malabou’s Hegel: One or several plasticities? - Moder Gregor (Filozofija i Društvo, 2015)
Through an original and extraordinarily fruitful reading of the Hegelian conception of negativity, Catherine Malabou developed the concept of plasticity which she keeps working on as one of her cardinal concepts even to this day. Engaging in the problematic of unity in Hegel, the paper takes on the task of trying to answer the question whether plasticity is one or are there several plasticities. The author argues that one must be careful not to reduce the inherent multiple of plasticity to a single plasticity which becomes plasticity par excellence: the plasticity of plastic explosion, of an abrupt and absolute break, to be distinguished from a creative or productive plasticity of habit. Malabou claimed that Hegel was - contrary to what Deleuz read in him - a philosopher of conceptual multitude as a multitude which cannot be reduced to only one image, the image of unity. If this is true, then the concept of plasticity itself with which she grasped the essence of Hegel’s dialectics, should be understood at least as a “unity in conflict”, if not as an inorganic, inhomogeneous, composed unity - and perhaps even as a unity of the pack.